ANALISIS PENGARUH SEKTOR PARIWISATA DAN PDRB TERHADAP PAD KABUPATEN/KOTA DI PROVINSI BALI - Ariani, Ni Made Putri; Utama, Made Suyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.03.TAHUN.2024DO - 10.24843/EEB.2024.v13.i03.p10, 2024)
The purpose of this study was to analyze the influence of the Tourism Sector and Gross Regional Domestic Product (GRDP) on the Regional Original Income (PAD) of districts/cities in Bali Province. This study uses panel data with time series data for 5 years from 2016-2020 and cross section data for 9 districts/cities in Bali Province so that the total observations are 45 observation points. The data used is secondary data with data collection methods, namely non-participant observation. The data collected was then analyzed using descriptive analysis techniques and multiple linear regression analysis. The results showed that the number of tourist visits, hotel occupancy rates, and GRDP had a positive and significant effect on the PAD of districts/cities in Bali Province, and the dominant independent variable that had an effect on PAD was GRDP